The Effect of Job Placement, Work Quality and Work Discipline on Employee Work Performance of PT. Shin Heung Indonesia - Kirani Arum Sari; Retno Purwani Setyaningrum (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2022)
The goal of this study is to examine the effect of placement, work quality and work discipline on the employee work performance of PT. Shin Heung Indonesia. This research utilized quantitative methods. Sampling was carried out using the saturated sample method by involving all the population as samples, thus the researchers obtained a sample of 50 people who were employees of PT. Shin Heung Indonesia. The analytical test tool used is SmartPLS v 3.2.6 with SEM (Structural Equation Modeling) analysis method. The results of this study indicate that the placement has a positive and significant effect on employee performance as indicated by the t-statistic value of 2.843, which is > 1.96 and the p-value of 0.005, which is < 0.05, work quality has a positive and significant effect on employee performance with a t-statistic value of 2,345, namely > 1.96 and a p-value of 0.019, which is < 0.05 and work discipline has a positive and significant effect on employee performance with a t-statistic value of 2.496, namely > 1.96 and a p-value of 0.013, which is < 0.05.